Palmilha sensora para a identificação do formato do pé - Girão, Natália Soares (2019)
This work presents the stages of development and testing of an instrumented insole with fiber Bragg gratings. The pressure patterns generated by the contact between the foot and the surface of the insole provided the identification of the anatomies of three different feet. The insole was produced by the incorporation of fiber Bragg gratings in silicone rubber. This material was chosen after the evaluation of characteristics such as Bragg gratings response and mechanical resistance suitable for the application. Artificial neural networks were used to perform the processing of the nonlinear and coupled responses provided by the contact between the insole and the feet. The best modeling used de data of 5 Bragg gratings, detecting 7 regions of the insole. For this case, the RNA made the correct association between output and target in 79% of the data samples during training stage.